Subclinical left ventricular dysfunction and N-terminal pro-brain natriuretic peptide in patients with rheumatoid arthritis - I. G. Kirillova; Yu. N. Gorbunova; T. V. Popkova; M. E. Diatroptov; E. L. Nasonov (Научно-практическая ревматология, 2022)
Aim – to determine the frequency of myocardial dysfunction using echocardiography with speckle tracking (STE) method, the relationship between a low global longitudinal strain (GLS) with the level of NT-proBNP, clinical and laboratory manifestations of rheumatoid arthritis. Material and methods. The study included 43 patients with RA (ACR/EULAR criteria, 2010): 79% women, age – 53.0 [38.0; 63.0] years, disease duration – 60.0 [36; 180] months; DAS28 – 5.9 [5.2; 6.4], positive for ACCP (74%), RF IgM (81%), without prior biological therapy and CVD. Methotrexate was received by 44%, leflunomide – 35%, sulfasalazine – 9.3%, hydroxychloroquine – 7%, glucocorticoids – 67.4%, non-steroidal anti-inflammatory drugs – 74% of patients with RA. All RA patients underwent echocardiography – tissue Doppler and STE. The level of NT-proBNP was determined in the blood serum The normal range for NT-proBNP was less than 125 pg/ml.Results. Low GLS was observed in 26 (61%) patients with RA. RA patients had a decrease GLS, E LV, E’ LV, E/A LV compared with the control group. Left ventricular diastolic dysfunction (LVDD) was higher in RA patients (13 (31%) vs 0%). Patients with RA had significantly higher levels of NT-proBNP (114.8 [45.1; 277.5] and 52 [40.5; 69.1] pg/ml) compared with the control group. There were correlations between a low GLS and DAS28 (r=0.9), the number of painful joints (r=0.6), radiological stage (r=0.6) and the presence of systemic manifestations (r=0.5), age (r=–0.9), E LV velocity (r=–0.5) (p<0.05 in all cases). There were correlations between the level of NT-proBNP and the E/A LV ratio (r=–0.4), A LV velocity (r=0.5) (p><0.05 in all cases).>< 0.05 in all cases). There were correlations between the level of NT-proBNP and the E/A LV ratio (r=–0.4), A LV velocity (r=0.5) (p< 0.05 in all cases).Conclusions. In RA patients with a high frequency the low GLS LV was detected, which is associated with a high activity of the inflammatory process. STE helps to detect myocardial dysfunction in patients with RA at earlier stages than tissue Doppler. The use of STE, the determination of the level of NT-proBNP make it possible to diagnosing preclinical disorders of systolic and diastolic functions of the LV, which can contribute to the early initiation of therapy and improve the prognosis in this category of patients.